Research of complex systems in machine building on the basis of structural matrix method - Bakay , Borys (Forestry, Forest, Paper and Woodworking Industry, 2017)
The use of the method of structural matrices for the structural representation and research of complex dynamic systems is proposed, which allows using the specific form of writing the matrix of coefficients, without resorting to additional graphic images, it is convenient to lay the foundations for building a system of any physical essence in mechanical engineering. The given method on the basis of the proposed algorithm and the standardized form of the structural matrix can be used to develop the structure of not only engineering systems. In the long term, the method of structural matrices will be widely used in the study of complex structures of mechanical engineering of those ecosystems. All these systems in sectoral engineering are complex systems, so their representation on structural matrices, with the reflection of direct and feedback, allows us to determine a number of unconsidered interactions before.